PENYELESAIAN DISHARMONI PERATURAN PERUNDANG-UNDANGAN MELALUI JALUR MEDIASI - Basuki Kurniawan; Nita Ryan Purbosari (Universitas Islam Negeri (UIN) Mataram, 2022)
The conflict of norms or disharmony the rules in Indonesia is a legal problem often happen. This case is because some rules from the substance overlap betwen the rules. The Dispute of Disharmony the rules with mediation is a perfect way from The Rule of Ministry of Law and Human Right Number 32 Year 2017 about Procedures of dipute solving the rules with Non Litigation . With the purpose to create harmonization the rules with mediation for product of law. This concept is born from a problem whereas many overlap regulation and the implication is created irregularity law in a society. So that reducing the existation of law as a the intergration to create harmony and compatibility as a way to fullfill interest of the people. The implication of mediation to solve the dishamony of rules as be setted by Pemermenkum 2/2019 can be seen on pressing the count of rules have conflict (ambivalensi) and be able to reducing count of the application of judicial review will submit to Supreme Law.